A Comparison Of Design Approach Using Topology Optimization Design And Parametric Design Of Suspended Handle With Multi Constraints Optimization For Vibration Attenuation - Lee, Wing Siong (Universiti Sains Malaysia, 2021)
Grass trimmer is a very common tool to clear the weeds. However, the high hand-arm vibration level has been reported when using the grass trimmer which is undesired as long-term exposure to the high hand-arm vibration level could lead to hand-arm vibration syndrome. There is scientific evidence that shows the use of suspended handle adaptor can reduce the hand-arm vibration effectively. In order to further improve the design, new suspended handle adaptors were designed with ABS plastic through topology optimization approach and parametric design approach. In term of natural frequency and stress level, the designs models from the guided and unguided topology optimization approach have a high natural frequency and stress level except the machined spring design. Whereas the machined spring type design models from parametric design approach have a relatively low natural frequency and stress level especially the 3 arm design models. From the vibration transmission aspect, the simulation result shows that the best machined spring type design models from guided topology optimization approach and parametric approach were able to reduce the acceleration level at the loop handle by 78.36% and 93.61% at the dominant operating frequency (103Hz). Based on the simulation result, design model (4d) from parametric design approach was chosen for prototype fabrication. The experimental result also has showed that using the prototype was able to reduce the acceleration transmissibility significantly in Xh, Yh and Zh axes. The acceleration transmissibility at the dominant operating frequency for the case with prototype was 63.99%, 86.67% and 87.09% lower in Xh, Yh and Zh axes as compared to the case without prototype.